Pragmatic Abilities of Children with Williams Syndrome: A Longitudinal Examination - John, Angela E.; Dobson, Lauren A.; Thomas, Lauren; Mervis, Carolyn B. (Frontiers in Psychology, 2012)
Although prior research has indicated that pragmatics is an area of particular weakness for individuals with Williams syndrome (WS), the relations among different pragmatic abilities and the relations between pragmatic ability and expressive vocabulary ability have yet to be addressed. In addition, analyses of the relations between the same type of pragmatic ability over time have not been reported. The present study was designed to address these questions. We considered the pragmatic language abilities of 14 children with WS at two time points: as 4-year-olds during a 30-minute play-session with their mothers (Time 1) and an average of 5.87 years later during a one-on-one conversation with a familiar researcher (Time 2). Children’s intellectual and expressive vocabulary abilities were assessed at both time points. Results indicated that the ability to verbally contribute information beyond what was required in response to a question was significantly related to the ability to verbally contribute new information in the absence of a question both at age 4 years and during primary school. At age 4, both the ability to pair verbalizations with eye contact (intersubjectivity) and expressive vocabulary ability were related to the ability to verbally contribute information beyond what was expected within a social interaction. Finally, the ability to verbally contribute new information to a social interaction beyond what was required to answer a question and the ability to pair verbalizations with eye contact (intersubjectivity) at age 4 years predicted the ability to verbally contribute new information beyond what was required to answer a question at age 9 – 12 years. The theoretical implications of our findings and the importance of early pragmatic language intervention for children who have WS are discussed.